L’Amérique latine dans le système mondial, 1950-1980 - Holly, Daniel (Études internationales, 1986)
This article is about the international relations of Latin America between 1950-1980. No systematic account of such history is attempted here. Rather attention is paid above all to the main thrust of such history. In this study it is argued that most dominated countries have very little capacity to affect the general and most fundamental structures of the World System. These countries tend to be mere object of history. There foreign policies to a very large extent contribute to the reproduction of the World System. Indeed it is one of the functions they must assume as far as the development of the system is concerned. But given the fact that underdeveloped countries are also subject of history, they do not submit passively to such a general law of social system. Their foreign policies are sometimes designed to modify the International Division of Labor "or their place within it" and with it the distribution of power without however drastically changing or upsetting the inner logic of the World System. It is within such an approach that one must study the international role of dominated countries in general and of the Latin American states in particular.